Optimasi Konsentrasi HCl Dan Suhu Kalsinasi Terhadap Yield Produk MgCl2 Dari Bittern - Annisa, Nur; Diah Nur Fitri Midayoga; Lilik Suprianti; Srie Muljani (Jurnal Serambi Engineering, 2026)
The brine solution remaining after salt crystallization contains high levels of valuable minerals, particularly magnesium, which can be extracted and processed into magnesium chloride (MgCl₂), a compound widely used in various industrial applications. This study examines the effect of hydrochloric acid (HCl) concentration and calcination temperature on the yield of MgCl₂ synthesized from brine-derived magnesium hydroxide. Magnesium hydroxide was precipitated using sodium hydroxide and subsequently reacted with HCl solutions of varying concentrations (1N–5N) before being calcined at temperatures ranging from 350°C to 550°C. The results show that both HCl concentration and calcination temperature significantly influence the product yield. The highest yield, 80.07%, was obtained at an HCl concentration of 4N and a calcination temperature of 550°C. While increasing acid concentration and temperature generally improved yield, concentrations above 4N did not provide further benefits and instead tended to decrease efficiency. These findings highlight key processing parameters for optimizing MgCl₂ production from brine, contributing to more efficient resource utilization and environmentally sustainable mineral processing practices.